Yield Performance and Nutrient Uptake of Red Rice Variety (MRM 16) at Different NPK Fertilizer Rates - Z. Masni; M. E. Wasli (International Journal of Agronomy)
Global demand for high-quality rice and healthy food has increased, especially to the affluent and health-conscious consumers. Red rice has been consumed because of its health benefits. Red rice has met the concepts of productivity and quality that emerged to supply the demands for products that improve the eating pattern of its consuming population. Red rice is based on food industries especially for nutrition-based food products and baby food products. For the case on Malaysia, limited domestic supplies of red rice have led to full dependency on imported red rice supplies in the country. Recent statistics showed that the Sarawak state can be one of the potential areas for the development of red rice production due to its vast land resources; proper guidelines which suit the agroecosystem in Sarawak for cultivation of red rice are essential. As for rice production in general, proper application of fertilizers enhances the yield and to a certain extent sustains soil productivity. Considering the needs to establish a proper fertilizing program especially for red rice production in Sarawak, a preliminary study was conducted to evaluate the yield and yield components of red rice variety (MRM 16) with three levels of NPK fertilizers (Treatment 1, control; Treatment 2, 60 : 35 : 40; Treatment 3, 120 : 70 : 80; and Treatment 4, 180 : 105 : 120 (proportions of N, P2O5, and K2O·ha−1, respectively)). The experiment was conducted in the pot trial during main season 2016 (December 2016–April 2017). The yield parameters including rice yield, panicle no./m2, 1000-grain weight, spikelet number per panicle, and percentage of filled spikelets were collected. The results showed that yield was not significantly affected by the increment of the NPK fertilizer added at a rate of more than 60 kg/ha N, 35 kg/ha P, and 40 kg/ha K (T2). From the study, it was observed that the yield and yield components of red rice variety (MRM 16) were best in T2 (60 kg/ha N, 35 kg/ha P, and 40 kg/ha K).